2018
DOI: 10.3389/fchem.2018.00307
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Atrazine Sorption to Biochar With Titration Calorimetry and Flow-Through Analysis: Implications for Design of Pollution-Control Structures

Abstract: Atrazine is one of the most common broad-leaf herbicides used in the world. However, due to extensive use for many years, atrazine often appears in surface and groundwater. Atrazine transport is inhibited by degradation or sorption to soil components, especially organic matter. Biochar is a charcoal-like material produced from pyrolysis of biomass. Due to the amount and type of functional groups found on biochar, this product has shown potential for sorption of atrazine from solution. There is an interest in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Fortunately, isothermal titration calorimetry (ITC) allows for the direct quantification of the binding association constant (K a ), enthalpy change (Δ H ), entropy change (Δ S ), and Gibbs free energy change (Δ G ) of a chemical process. Most commonly, researchers in the biological sciences use this technique to investigate substrate-active site interactions. , Similarly, we envisioned the value of this technique for illuminating adsorptive processes in MOFs. Only recently have materials chemists begun exploring the applicability of this technique for the study of porous sorbents. Therefore, we undertook a proof-of-concept study using ITC to explore the parameter space of glyphosate adsorption in Zr-MOFs (Figure ). Glyphosate, the active ingredient of the widely used pesticide Roundup, possesses both a carboxylic acid and a phosphonic acid .…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, isothermal titration calorimetry (ITC) allows for the direct quantification of the binding association constant (K a ), enthalpy change (Δ H ), entropy change (Δ S ), and Gibbs free energy change (Δ G ) of a chemical process. Most commonly, researchers in the biological sciences use this technique to investigate substrate-active site interactions. , Similarly, we envisioned the value of this technique for illuminating adsorptive processes in MOFs. Only recently have materials chemists begun exploring the applicability of this technique for the study of porous sorbents. Therefore, we undertook a proof-of-concept study using ITC to explore the parameter space of glyphosate adsorption in Zr-MOFs (Figure ). Glyphosate, the active ingredient of the widely used pesticide Roundup, possesses both a carboxylic acid and a phosphonic acid .…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, we observed good fits to the BET, Freundlich and Langmuir models, indicating non-linear sorption. In the literature, good fits to Langmuir have been reported for tetracycline ( Jang and Kan, 2019 ), enrofloxacin ( Zhao et al, 2019 ) or atrazine ( Penn et al, 2018 ). Nonetheless, the fits to the Freundlich isotherm were often of similar quality, and such behavior was confirmed in terms of atrazine sorption on soils ( Yue et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Lower pH might be an advantageous factor for the sorption of ionizable substances (Oh and Seo, 2016;Mandal et al, 2017), which proposes the role of negative surface charges in the biochar adsorption capacity. In a study by Penn et al (2018), it was reported that pH did not affect the sorption process and heat release. The atrazine-biochar solution with a neutral pH does not alter the state of atrazine, thus reducing the possibility of cationic exchange in the sorption process (Weber, 1993).…”
Section: Biochar As Adsorbent For Atrazine Removalmentioning
confidence: 97%
“…However, the sorption capacities of biochar for atrazine largely depend on feedstock sources, pyrolysis temperature, rate of pyrolysis, and resident time. Moreover, the type and number of surface functional groups (Penn et al, 2018), surface area, and strong binding affinity may also influence the sorption potential of biochar for atrazine (Zhao et al, 2013;Mandal et al, 2017). Biochar's sorption capacities for atrazine vary largely with the type of feedstock used for biochar production.…”
Section: Biochar As Adsorbent For Atrazine Removalmentioning
confidence: 99%